RESEARCH OF DRIED DATES PRODUCTION TECHNOLOGY - Xojiev Adxam; Choriev Abdusattar (Journals Park Publishing, 2022)
Date varieties were studied and selected for drying. Dates are dried in a combinatorial way. The change in the moisture content of dates in time has been studied.
Keywords: palm tree; drying; equipment